Encouraging Innovation Capability through Entrepreneurship Orientation: The Role of Absorptive Capacity and Improvisation as Mediation - Selly Saliyah Hartati Utami; Riani Rachmawati (Fakultas Ekonomi Dan Bisnis Universitas Pelita Harapan, 2022)
Uncertainty arises as a result of changing environmental conditions, and the company must be able to adapt to these changes by encouraging innovation. Innovation capability is required in order to encourage innovation, because innovation capability is a company's ability to innovate. Several previous studies examined the role of entrepreneurial orientation, absorptive capacity, and improvisation on innovation capability; however, in previous studies, entrepreneurial orientation was tested at the organizational level with the dimensions of risk taking, proactiveness, and innovativeness, whereas in this study, we attempted to examine entrepreneurial orientation at the individual level by adding passion and perseverance as a dimension. The context of this research is also carried out in one of the companies, which is a State-Owned Enterprise (SOEs), where several studies have views on the low innovation capability of SOEs. In this study, we attempt to investigate empirically the effect of individual entrepreneurial orientation on innovation capability in the business unit at PT Kawasan Berikat Nusantara (Persero), a state-owned enterprise engaged in industrial estate services. The study's findings show that an individual entrepreneurial orientation, as mediated by absorptive and improvisational abilities, can influence innovation capability. This research is expected to benefit the company by maximizing its absorptive capacity and improvisation ability, as well as paying attention to the entrepreneurial orientation of the individual in the company.